2011
DOI: 10.1093/cercor/bhq267
|View full text |Cite
|
Sign up to set email alerts
|

Vision of the Body Modulates Somatosensory Intracortical Inhibition

Abstract: The magnitude of somatosensory evoked potentials (SEPs) elicited by simultaneous electrical stimulation of adjacent digits is generally less than the sum of potentials evoked by stimulation of each digit individually. This under-additivity suggests suppression between representations of adjacent skin regions and may reflect a process of lateral inhibition by interneurons in somatosensory cortex. Given that simply viewing the body enhances tactile acuity and that tactile acuity depends on cortical lateral inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
116
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 98 publications
(130 citation statements)
references
References 51 publications
13
116
1
Order By: Relevance
“…Considering both previous evidence (Cardini et al, 2013(Cardini et al, , 2011Longo et al, 2009) and the present findings, we speculate that promoting stable representation of the body -by delivering coherent body-related inputs -might consequently induce sharpening in somatosensory maps, potentially improving tactile sensitivity and reducing pain. Conversely, distorted bodily representation, evoked by co-occurrence of discrepant signals, could be responsible for somatosensory blurring, eventually affecting tactile discrimination ability and causing or exacerbating pain.…”
Section: Intracortical Inhibition and Visual Modulation Of Somatosenssupporting
confidence: 79%
See 4 more Smart Citations
“…Considering both previous evidence (Cardini et al, 2013(Cardini et al, , 2011Longo et al, 2009) and the present findings, we speculate that promoting stable representation of the body -by delivering coherent body-related inputs -might consequently induce sharpening in somatosensory maps, potentially improving tactile sensitivity and reducing pain. Conversely, distorted bodily representation, evoked by co-occurrence of discrepant signals, could be responsible for somatosensory blurring, eventually affecting tactile discrimination ability and causing or exacerbating pain.…”
Section: Intracortical Inhibition and Visual Modulation Of Somatosenssupporting
confidence: 79%
“…Further, we recently showed that vision of the stimulated hand, compared to vision of a non-body object, increases somatosensory suppression, as well as enhancing tactile sensitivity on the observed location (Cardini et al, 2011).…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations